ANALISIS KESULITAN SISWA DALAM KEMAMPUAN KOMUNIKASI MATEMATIS PADA MATERI PERSAMAAN GARIS LURUS - Maulani, Nuril; Sukirwan; Dedi Muhtadi (Universitas Islam Nusantara, 2025)
This study aims to analyze the types of difficulties encountered by students in solving linear equation problems in relation to their mathematical communication skills. A qualitative approach with a descriptive method was employed. The research subjects consisted of 30 eighth-grade students from a junior high school in Tasikmalaya, selected purposively. Research instruments included a written test to identify students’ difficulties in mathematical communication and a guided interview protocol to explore the underlying causes of these difficulties. Data were analyzed using thematic analysis and triangulation techniques to ensure validity and reliability. The findings revealed three primary categories of student difficulties: (1) difficulty in representing linear equations graphically due to limited understanding of coordinate systems and variable relationships; (2) difficulty in clearly articulating mathematical reasoning, indicating weak verbal communication skills; and (3) difficulty in formulating mathematical models from contextual problems, demonstrating a reliance on procedural strategies without conceptual understanding. The discussion highlights that these communication challenges stem from instruction that overemphasizes procedural outcomes and provides limited opportunities for students to engage in reflective mathematical discourse. The study implies the need for communicative, concept-based learning designs that integrate real-world contexts, emphasize multiple representations, and promote reflective practices. It is recommended that teachers incorporate collaborative learning strategies and interactive visual media to foster students’ mathematical communication skills, particularly in algebraic contexts.